Luigi Meneghello La biosfera e il racconto - Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2017)
Between Luigi Meneghello's writing and the natural world there is an implicit yet profound bound, destined to reverberate in the folds of the text, giving rise to unprecedented and transversal readings. And eco-criticism, in this case, far from being but a privileged starting point, it also takes on the task of reflecting more deeply on what, on balance, are the salient features of the eco-writer Meneghello: from th environmental emergency, to the semantics of places; from the conception of the text as an 'ecosystem', to stories about things and matter; and then, the second part of the volume deals with the story of the animal kingdom, aimed at redefining the value structure of theHomo sapiens and its place in this narrated biosphere.